Solar wind ion trends and signatures: STEREO PLASTIC observations approaching solar minimum - A. B. Galvin; M. A. Popecki; K. D. C. Simunac; L. M. Kistler; L. Ellis; J. Barry; L. Berger; L. M. Blush; P. Bochsler; P. Bochsler; C. J. Farrugia; L. K. Jian; et al. (Annales Geophysicae, 2009)
STEREO has now completed the first two years of its mission, moving from close proximity to Earth in 2006/2007 to more than 50 degrees longitudinal separation from Earth in 2009. During this time, several large-scale structures have been observed in situ. Given the prevailing solar minimum conditions, these structures have been predominantly coronal hole-associated solar wind, slow solar wind, their interfaces, and the occasional transient event. In this paper, we extend earlier solar wind composition studies into the current solar minimum using high-resolution (1-h) sampling times for the charge state analysis. We examine 2-year trends for iron charge states and solar wind proton speeds, and present a case study of Carrington Rotation 2064 (December 2007) which includes minor ion (He, Fe, O) kinetic and Fe composition parameters in comparison with proton and magnetic field signatures at large-scale structures observed during this interval.